2013
DOI: 10.1186/1479-5876-11-97
|View full text |Cite
|
Sign up to set email alerts
|

Multiple therapeutic peptide vaccines consisting of combined novel cancer testis antigens and anti-angiogenic peptides for patients with non-small cell lung cancer

Abstract: BackgroundVaccine treatment using multiple peptides derived from multiple proteins is considered to be a promising option for cancer immune therapy, but scientific evidence supporting the therapeutic efficacy of multiple peptides is limited.MethodsWe conducted phase I trials using a mixture of multiple therapeutic peptide vaccines to evaluate their safety, immunogenicity and clinical response in patients with advanced/recurrent NSCLC. We administered two different combinations of four HLA-A24-restricted peptid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 34 publications
0
39
0
Order By: Relevance
“…Several recent studies including our own have shown that good PS is a significant prognostic factor. 29,43,44 Regarding multiple peptide therapy, as we mentioned previously, recent data showed the effectiveness of vaccines containing multiple epitopes. More recently, dendritic cell immunotherapy using multiple epitopes has also been reported in the treatment of brain tumors.…”
Section: Future Perspectivesmentioning
confidence: 87%
See 1 more Smart Citation
“…Several recent studies including our own have shown that good PS is a significant prognostic factor. 29,43,44 Regarding multiple peptide therapy, as we mentioned previously, recent data showed the effectiveness of vaccines containing multiple epitopes. More recently, dendritic cell immunotherapy using multiple epitopes has also been reported in the treatment of brain tumors.…”
Section: Future Perspectivesmentioning
confidence: 87%
“…29 In this phase I study, we administered five kinds of peptides that originated from novel cancer-testis antigens and were developed from vascular endothelial growth factor receptors using a microarray-based technique. If the patients responded against multiple peptides, survival rate was significantly better than that in patients who responded to a single peptide or no peptides (P = 0.00176).…”
Section: Multiple Peptide Vaccinementioning
confidence: 99%
“…This report highlights two important issues for cancer vaccination, which are biomarker analysis and combination therapy. In our past study of multiple peptide vaccines for patients with NSCLC, we observed that the specific CTL responses against one or more epitopes could be a prognostic biomarker (9). Like this study, most immunotherapy studies were focused on CTL responses as a prognostic biomarker, however, there has not been a predictive biomarker for cancer vaccination before treatment.…”
mentioning
confidence: 83%
“…Antigen-specific immunotherapy places selective pressure on the tumor, which in turn can down-regulate expression of those antigens (or even of MHC I) during immunotherapy. To avoid antigen selection, vaccines can contain multiple defined epitopes that induce broader T-cell immunity; several multipeptide vaccines have already shown promising clinical results (20,21). Furthermore, because central tolerance mechanisms often destroy those T cells with the highest avidity to such selfantigens, vaccine-induced effector CD8 + T-cell responses against self tumor antigens are often weak at best (22).…”
Section: Vaccines and Antigen Selectionmentioning
confidence: 99%